Comprehensive evaluation of autohydrogenotrophic membrane biofilm reactor treating OTC-enriched water medium - Celik, Aytekin; Tunc, Muslun Sara; Hanay, Ozge; Taskan, Ergin; Hasar, Halil (Springer, 2018)
In the recent years, there has been considerable debate about the potential impacts of antibiotics present in various environments on the public health and ecology. Oxytetracycline (OTC) is one of tetracycline antibiotic group used for growth and treatment of animals and humans. In this study, OTC and nitrate (NO3-N) were simultaneously reduced using a hydrogen-based membrane biofilm reactor (H-2-MBfR). The system successfully accomplished OTC and nitrate removals. The fluxes of OTC and NO3-N were 8.96 mg OTC/m(2) day and 1100 mg N/m(2) day, respectively. On the other hand, the fluxes of H-2 utilized for OTC and NO3-N reductions were calculated as maximum values of 1.71 and 395 mg H-2/m(2) day, respectively. The concentrations of transformation products of OTC formed at ppb levels. The dominant species in all the experimental periods with OTC biodegradation referred to Naxibacter sp., Uncultured Beta proteobacterium, Janthinobacterium sp. and Alicycliphilus denitrificans in autotrophic biofilm community degrading OTC.
Keywords: Oxytetracycline; Autohydrogenotrophic denitrification; Advanced biological degradation; Polymerase chain reaction